Process Engineering and Glycosyltransferase Improvement for Short Route Chemoenzymatic Total Synthesis of GM1 Gangliosides. Issue 25 (17th March 2023) - Yu, Hai; Zhang, Libo; Yang, Xiaohong; Bai, Yuanyuan; Chen, Xi
Abstract: Large‐scale synthesis of GM1, an important ganglioside in mammalian cells especially those in the nervous system, is needed to explore its therapeutic potential. Biocatalytic production is a promising platform for such a purpose. We report herein the development of process engineering and glycosyltransferase improvement strategies to advance chemoenzymatic total synthesis of GM1. Firstly, a new short route was developed for chemical synthesis of lactosylsphingosine from the commercially available Garner's aldehyde. Secondly, two glycosyltransferases including Campylobacter jejuni β1–4GalNAcT (CjCgtA) and β1–3‐galactosyltransferase (CjCgtB) were improved on their soluble expression in E. coli and enzyme stability by fusing with an N‐terminal maltose binding protein (MBP). Thirdly, the process for enzymatic synthesis of GM1 sphingosines from lactosylsphingosine was engineered by developing a multistep one‐pot multienzyme (MSOPME) strategy without isolating intermediate glycosphingosines and by adding a detergent, sodium cholate, to the later enzymatic glycosylation steps. Installation of a desired fatty acyl chain to GM1 glycosphingosines led to the formation of target GM1 gangliosides. The combination of glycosyltransferase improvement with chemical and enzymatic process engineering represents a significant advance in obtaining GM1 gangliosides containing different sialic acid forms by total chemoenzymatic synthesis in a short route and with high efficiency. Abstract : Chemoenzymatic total synthesis of GM1 gangliosides : Combined process engineering and biocatalyst improvement strategies are developed for chemoenzymatic total synthesis of GM1 gangliosides from ( S )‐Garner's aldehyde. Two key glycosyltransferases are improved on their soluble expression in E. coli and enzyme stability. The multistep one‐pot multienzyme (MSOPME) process with the addition of a detergent in the latter glycosylation steps have been found to be highly efficient for obtaining GM1 gangliosides containing different sialic acid forms.